Epidermal-specific deletion of CD44 reveals a function in keratinocytes in response to mechanical stress - Shatirishvili, Marine; Burk, Alexandra Serena; Breuhahn, Kai; Tanaka, Motomu (Cell death & disease, 2016)
CD44, a large family of transmembrane glycoproteins, plays decisive roles in physiological and pathological conditions. CD44 isoforms are involved in several signaling pathways essential for life such as growth factor-induced signaling by EGF, HGF or VEGF. CD44 is also the main hyaluronan (HA) receptor and as such is involved in HA-dependent processes. To allow a genetic dissection of CD44 functions in homeostasis and disease, we generated a Cd44 floxed allele allowing tissue- and time-specific inactivation of all CD44 isoforms in vivo. As a proof of principle, we inactivated Cd44 in the skin epidermis using the K14Cre allele. Although the skin of such Cd44Δker mutants appeared morphologically normal, epidermal stiffness was reduced, wound healing delayed and TPA induced epidermal thickening decreased. These phenotypes might be caused by cell autonomous defects in differentiation and HA production as well as impaired adhesion and migration on HA by Cd44Δker keratinocytes. These findings support the usefulness of the conditional Cd44 allele in unraveling essential physiological and pathological functions of CD44 isoforms.
Gesehen am 06.05.2020